An inconvenient impact: Unveiling the overlooked differences in crystalline forms of iron (hydro)oxides on anaerobic digestion - Han-Quan Wen; Guan-Lin Chen; Yu-Sheng Li; Tian Tian; Yuan Pan; Han-Qing Yu (Water Research X)
Iron (hydro)oxides are commonly used to enhance anaerobic digestion due to their cost-effectiveness and versatility. However, the influence of crystalline structure on digestion performance is often overlooked despite their unique characteristics. In this study, we investigated how different crystalline forms of FeOOH affect substrate utilization, sludge activity, and the microbiomes in up-flow anaerobic sludge blanket (UASB) reactors. The crystalline structure of FeOOH impacted reactor performance, with γ-FeOOH, β-FeOOH, and α-FeOOH showing decreasing effectiveness, as reflected in chemical oxygen demand (COD) removal efficiencies of 99.0 %, 98.3 % and 97.1 %, respectively. FeOOH crystals influenced the secretion of extracellular polymeric substances (EPS) and sludge activity by releasing Fe ions at varying rates, leading to Fe accumulation in EPS in the order of β-FeOOH > γ-FeOOH > α-FeOOH. Additionally, γ-FeOOH supported the most stable microbial community structure, as indicated by the highest Alpha diversity index. This stability was associated with increased levels of Mesotoga and Syntrophus, along with the highest coenzyme F420 activity, which was approximately twice as high as in other groups. These findings underscore the crucial role of the crystalline structure of iron oxides in enhancing anaerobic digestion, emphasizing that biocompatibility should be a priority when optimizing digestion performance.